DISTRIBUTION OF ABO BLOOD GROUPS IN IRAN - K.Montazemi (Tehran University of Medical Sciences, 1978)
During the period 2530-36, population and health studies have been carried out by the School of Public Health and Institute of Public Health Research in different parts of Iran (Roodsar, Gonbad-Kavoos, Western Azarbaijan, Isfahan, Ghasghai tribe and Saheli Province). Genetic aspects including the distribution of ABO blood groups and Rh in various populations was specially considered in these surveys. Sampling was fulfilled on the basis of "stratified cluster sampling" in all the above mentioned areas. A total of 17,659 blood groups O,A,B and AB at the rate of 39.7, 25.4 and 6.2 per cent and also Rhesus positives and negatives at 93.1 and 6.9 per cent respectively. Regarding the distribution of ABO blood group in some populations we have found our results similar to those of Asiatic Indians and European gypsies. Also, comparison of the results showed the lowest incidence of Rhesus-negatives in Turkamans (1.5 per cent).